Shear thinning behavior of cerebrospinal fluid with elevated protein or cellular concentration - Hollister, John C. P.; Wang, Anthony C.; Kim, Won; Giza, Christopher C.; Prins, Mayumi L.; Kavehpour, H. Pirouz (Frontiers in Physics, 2023)
Introduction: Cerebrospinal fluid (CSF) plays a crucial role in the maintenance of the central nervous system (CNS) by cushioning the brain, providing nutrients, removing interstitial waste, and maintaining homeostasis. Flow characteristics of CSF may significantly contribute to brain dynamics, injury mechanics, disease pathogenesis, and the functionality of the glymphatic system. Conventionally, CSF is considered to have very similar rheological properties to water and Newtonian behavior of CSF has been assumed, despite its complex composition, which can include proteins like albumin and tau, as well as cellular content such as blood. Methods: Recent advances in rheological techniques allow for more accurate quantification of CSF characteristics and behavior. Here, we present an updated rheological characterization of CSF, including the impact of its cellular and proteinaceous constituents. CSF samples were tested for protein and cellular concentration. Using precision torsional rheometry and recently developed extensional rheology techniques, we show that CSF with elevated cellular or protein concentration exhibits significant non-Newtonian behavior, especially at low shear rates. Results: Like other biological fluids, CSF with elevated cellular or protein concentration exhibits shear thinning behavior until reaching a steady state viscosity of approximately 1 mPa·s at shear rates greater than 10 s-1. This shear thinning behavior becomes more pronounced with increasing concentration of its constituents. In extensional flow, CSF exhibited weakly non-Newtonian behavior, with an average extensional relaxation time of 0.14 ms. The extensional relaxation time is positively correlated to cellular concentration and significantly increased with elevated protein. Discussion: Our results enhance the understanding of CSF rheology with significant implications for the analysis, modeling, and treatment of CSF-related processes.